RELATIVE CAPITALIST SYSTEMS AND FAIRNESS IN THE BALTICS: THE CASE OF LITHUANIA - Huettinger, Maik; Zirgulis, Aras (Ekonomika, 2013)
Abstract. This paper deals with the concept of fairness as it is applied to economic decision making in different cultures. The objective of the research is to determine whether the concept of fairness can be applied universally throughout all cultures by doing a study in Lithuania and comparing it to similar studies done in other countries. Lithuania was chosen because it belongs to the group of the Baltic advanced transition countries with their own unique form of capitalism. We find that Lithuanians are more apt to consider price or wage changes as fair as long as there is an underlying macroeconomic reasoning for the price change. These effects were found to hold true in spite of the framing effects of loss aversion found in previous studies. Key words: behavioral economics, fairness, capitalism, Baltics, Lithuania